2022
DOI: 10.3389/fpubh.2022.981245
|View full text |Cite
|
Sign up to set email alerts
|

Parental smartphone addiction and adolescent smartphone addiction by negative parenting attitude and adolescent aggression: A cross-sectional study

Abstract: IntroductionThis study aimed to examine the mediating role of negative parenting attitudes and adolescent aggression in the relationship between parents' and adolescents' smartphone addiction.MethodsThis was a cross-sectional descriptive study that used data from the 2018 Korean Children and Youth Panel Survey. The study involved 2,360 adolescents (1,275 boys, 54.0%, mean age 14.52 ± 0.33 years) and their parents (2,148 mothers, 91.0%), who used smartphones. Adolescents completed questionnaires assessing negat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 54 publications
(88 reference statements)
0
2
0
Order By: Relevance
“…Thus, their behaviors are largely susceptible to the influence of their surroundings [ 102 ]. From the perspective of environmental interaction, some research indicates that the time mothers spend with their adolescent children and the quality of parent-child interaction play a significant role in adolescents' smartphone use [ 103 ], but these kinds of interventions and prevention strategies are not systematically addressing the surroundings' influences. In our research, we applied an institutional perspective to explain adolescent smartphone overuse, which can provide a more comprehensive understanding of how external institutional environments impact the adolescents’ digital behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, their behaviors are largely susceptible to the influence of their surroundings [ 102 ]. From the perspective of environmental interaction, some research indicates that the time mothers spend with their adolescent children and the quality of parent-child interaction play a significant role in adolescents' smartphone use [ 103 ], but these kinds of interventions and prevention strategies are not systematically addressing the surroundings' influences. In our research, we applied an institutional perspective to explain adolescent smartphone overuse, which can provide a more comprehensive understanding of how external institutional environments impact the adolescents’ digital behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Parents also can be a factor to affects the children's smartphone use pattern. According to Doo, E. Y. and Kim, J. H., they found that parenting altitude is related to the addiction to cell phones, which means a good parenting attitude may lead to positive smartphone usage patterns [9]. Therefore, a good attitude toward parenting does influence children and adolescents.…”
Section: Value Family Influencementioning
confidence: 99%